2021
DOI: 10.1039/d1py00074h
|View full text |Cite
|
Sign up to set email alerts
|

Well-defined polyvinylpyridine-block-polystyrene diblock copolymers via RAFT aqueous-alcoholic dispersion polymerization: synthesis and isoporous thin film morphology

Abstract: In this work, the synthesis and characterization of polyvinylpyridine-polystyrene (PVP-b-PS) diblock copolymers via reversible addition-fragmentation chain transfer (RAFT) dispersion polymerization is presented. A series of poly(4-vinylpyridine) (P4VP) and poly(2-vinylpyridine) (P2VP)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 75 publications
2
24
0
2
Order By: Relevance
“…Especially RAFT emulsion and dispersion polymerization techniques have become a powerful tool for the efficient synthesis of the diblock copolymer. They provide an efficient heat transfer, a low viscosity during the entire reaction time and enable the production of well-defined polymers with high molar masses and nar-Polymers 2022, 14, 62 3 of 23 row dispersity [37,[41][42][43][44][45]. RAFT-mediated polymerization-induced self-assembly (PISA) has been studied thoroughly by a variety of scientific groups such as Armes et al [46], Troung et al [47], and Boyer et al [48], to name a few, effectively advancing the research in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Especially RAFT emulsion and dispersion polymerization techniques have become a powerful tool for the efficient synthesis of the diblock copolymer. They provide an efficient heat transfer, a low viscosity during the entire reaction time and enable the production of well-defined polymers with high molar masses and nar-Polymers 2022, 14, 62 3 of 23 row dispersity [37,[41][42][43][44][45]. RAFT-mediated polymerization-induced self-assembly (PISA) has been studied thoroughly by a variety of scientific groups such as Armes et al [46], Troung et al [47], and Boyer et al [48], to name a few, effectively advancing the research in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Nieswandt et al successfully prepared P2VP–PS and P4VP–PS via RAFT aqueous-alcoholic dispersion polymerization using P2VP and P4VP as macro-CTAs, respectively. 38 Copolymers with high molar mass (>100 kg mol −1 ) could be achieved in both cases, but the P4VP–PS had broader molar mass distributions. Nieswandt et al also reported the preparation of poly(3-vinylpyridine)-poly(styrene) (P3VP–PS) via RAFT emulsion polymerization in DMF/H 2 O (50/50, v/v) solvent mixtures.…”
Section: Introductionmentioning
confidence: 97%
“…39 However, in all of the reports described above, block copolymer nanoparticles were formed via self-assembly of the copolymers in selective solvents. Although, Nieswandt et al claimed that P2VP–PS, 38 P4VP–PS, 38 and P3VP–PS 39 can be successfully prepared via RAFT-mediated PISA, they did not investigate these block copolymer nanoparticles directly. Instead, these copolymers were dissolved in THF and precipitated in an excess of ice-cold n -hexane to obtain nanoparticles, and the bulk and surface morphologies of the diblock copolymers were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…13–15 In addition, the pyridine-containing BCPs with excellent stability, rigidness and facile functionalization make them excellent precursors for the construction of complex, highly-ordered and functional polymeric nanostructures for different applications. 16–19 Various kinds of pyridine-containing BCP nano-assemblies in aqueous solution have been constructed through the traditional solvent exchange method. 20,21 However, it still remains a critical challenge to design and fabricate pyridine-containing block polymeric nano-assemblies in a large scale in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%